Effect of Pre-exposure Prophylaxis to Reduce the Chances of Human Immuno-Deficiency Virus Infection among the Key Populations - Barik, Sushanta Kumar; Vijay, Mulay Manjushree; Kulkarni, Smita Sitaram; Turuk, Jyotrimayee; Mohanty, Keshar Kunja; Jena, Srikanta; Harke, Sanjay N.; Deshmukh, Ashish S.; Dhoble, Sanjay J.; Khemnar, Annasaheb S. (Disease and Health Research: New Insights Vol. 3, 2024)
The key populations (KPs) such as female sex workers (FSWs), transgender communities (TGs), persons who inject drugs (PWID), men who have sex with men (MSM), heterosexual groups (HGs) are easily vulnerable to human immunodeficiency virus (HIV) infections. The use of pre-exposure prophylaxis (PrEP) could reduce the chances of HIV infections in the KPs. PrEP can be used as an HIV prevention tool to reduce the infections in HIV burden countries of the world. Awareness and expression of willingness to use PrEP is an additional HIV prevention and works like a complement tool for KPs who are unable to use condoms consistently. PrEP could be used as a main tool in HIV testing and services among the KPs in the Integrated Counselling and Testing Centre (ICTC) and Antiretroviral Therapy (ART) centre. The main determining factors for the use of PrEP are awareness, availability, accessibility, and affordability among the KPs. The most challenging issues such as the burden of stigma and discrimination, noncommunity-friendly therapy dispensing areas and interrupted supply of therapies were identified as key barriers to continuing PrEP. The introduction and recommendation of PrEP into various programs, stakeholders and policymakers could impact HIV prevention among the KPs. However, the use of PrEP as a tool among the KPs is very needful to reduce the burden of new HIV infections.